Answer:
x = 0 and x = 1
Step-by-step explanation:
From the table of values
f(x) = g(x) = 1 when x = 0 , and
f(x) = g(x) = 0.25 when x = 1
The solution to f(x) = g(x) are x = 0 and x = 1
Answer:
Nonlinear system of inequalities
Step-by-step explanation:
For this case we have the following expression:
![\sqrt [3] {5x-2} - \sqrt [3] {4x} = 0](https://tex.z-dn.net/?f=%5Csqrt%20%5B3%5D%20%7B5x-2%7D%20-%20%5Csqrt%20%5B3%5D%20%7B4x%7D%20%3D%200)
If we add to both sides of the equation
we have:
![\sqrt [3] {5x-2} = \sqrt [3] {4x}](https://tex.z-dn.net/?f=%5Csqrt%20%5B3%5D%20%7B5x-2%7D%20%3D%20%5Csqrt%20%5B3%5D%20%7B4x%7D)
To eliminate the roots we must raise both sides to the cube:
![(\sqrt [3] {5x-2}) ^ 3 = (\sqrt [3] {4x}) ^ 3\\5x-2 = 4x](https://tex.z-dn.net/?f=%28%5Csqrt%20%5B3%5D%20%7B5x-2%7D%29%20%5E%203%20%3D%20%28%5Csqrt%20%5B3%5D%20%7B4x%7D%29%20%5E%203%5C%5C5x-2%20%3D%204x)
So, the correct option is the option c
Answer:
Option C
Hi I just don't care I uf to answer
Answer:
y = 3x + 5
Step-by-step explanation:
The slope of this line is (11 - (-4)) / (2 - (-3))
= 15/5 = 3
Now we use the point slope form of an equation:-
y - y1 = m(x - x1)
y - 11 = 3(x - 2)
y - 11 = 3x - 6
y = 3x + 5 (answer)